POLITIK HUKUM PENGATURAN WEWENANG PSIKOLOG DAN ILMUWAN PSIKOLOGI DALAM PENYAMPAIAN PERNYATAAN MELALUI MEDIA MASSA TERKAIT DENGAN PSIKOLOGI FORENSIK (Jurnal Magister Hukum Perspektif, 2019)
This article wants to find the legal politics of authorizing forensic psychologists to make statements on client data in the media as stipulated in the Indonesian Code of Ethics of Psychology. Consistency between regulations in the code of ethics in formulating objectives and achieving regulatory objectives needs to be studied, as well as consistency between the content of the code of ethics regulations and the content of applicable laws and regulations in Indonesia. Forensic psychology is part of 18 sub-fields of psychology. Forensic Psychology services can be performed by a psychologist of one psychological scientist to assist law enforcement in legal proceedings inside and outside the court, research and educational needs. Based on the study of legal politics, it can be found that the legal regulations contained in the Code of Ethics are clearly intended to help law enforcement, researchers, and educators to understand phenomena, but the process and content of forensic psychologist statements on clients must always protect client privacy. Normatively, there are no inconsistencies in all regulations in the code of ethics, and all the contents of the code of ethics are in harmony with the laws and regulations governing education, research, law enforcement, and confidentiality of personal data. Thus, from the study of legal politics has been found consistency between goals, ways, and efforts so that it is clearly illustrated the politics of law granting authority, namely for the development of education and law enforcement without disturbing client privacy. Keywords: Legal Politics, Psychologist, Psychology Scientist, Mass Media, Forensic Psychology